Fluid and Thermal Sciences A Practical Approach for Students and Professionals - Nandagopal, PE, Nuggenhalli S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This text provides a clear understanding of the fundamental principles of thermal and fluid sciences in a concise manner in a rigorous yet easy to follow language and presentation. Elucidation of the principles is further reinforced by examples and practice problems with detailed solutions. Firmly grounded in the fundamentals, the book maximizes readers$1 (Bcapacity to take on new problems and challenges in the field of fluid and thermal sciences with confidence and conviction. Standing also as a ready reference and review of the essential theories and their applications in fluid and thermal sciences, the book is applicable for undergraduate mechanical and chemical engineering students, students in engineering technology programs, as well as practicing engineers preparing for the engineering license exams (FE and PE) in USA and abroad. Explains the concepts and theory with a practical approach that readers can easily absorb; Provides the just the right amount of theoretical and mathematical background needed, making it less intimidating for the reader; Covers fluid and thermal sciences in a straight-forward yet comprehensive manner facilitating a good understanding of the subject matter; Includes a wide spectrum and variety of problems along with numerous illustrative solved examples and many practice problems with solutions.s
Fluid Properties and Units -- Fluid Statics -- Fluid Dynamics -- Energy Equation -- Fluid Measurements -- Compressible flow -- Dimensional Analysis and Similitude -- Heat Transfer Principles -- Conduction Heat Transfer -- Convection heat transfer -- Radiation heat transfer -- Heat Exchangers -- Fundamentals -- Energy Balance and I Law -- Steam -- Fuels and Combustion -- Basic Cycles -- Power Generation Cycles.
Keywords: Production engineering; Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Industrial engineering; Thermal Process Engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Industrial and Production Engineering; Fluid dynamics; Thermodynamics